Cervical cerclage in twin pregnancies: An updated systematic review and meta-analysis. (May 2021) - Liu, Yijun; Chen, Meng; Cao, Tiantian; Zeng, Shuai; Chen, Ruixin; Liu, Xinghui
Highlights: Previous meta-analyses included few or low-quality literature, and the conclusions obtained were limited. Therefore, it is necessary to conduct the latest systematic review and meta-analysis. The articles included in our meta-analysis had a sufficient sample size, were of high quality, and reached some reasonable conclusions. Following the Preferred Reporting Items for Systematic reviews and Meta-Analyses statement, strictly setting up the inclusion and exclusion criteria, extracting a considerable part of the maternal and neonatal outcomes, using reasonable data processing software, and comprehensively evaluate the role of cervical cerclage in preventing preterm birth for twin pregnancies. Last but not least, our study makes a significant contribution to the literature because we report that when the cervical length was less than 15 mm, the risk ratio of preterm birth at < 37 weeks, <34 weeks, and <32 weeks of gestation was significantly lower in the cerclage group than in the non-cerclage group. We believe that this paper will be of interest to the readership of your journal because it provides a basis for the choice of clinical treatment methods and the limitation proposed in this meta-analysis will also inspire researchers. Abstract: Objective: Data on the prevention of preterm birth in twin pregnancies with cervical cerclage remain inconsistent. Thus, this study aimed to comprehensively evaluate the value of cervical cerclage as a treatment strategy to prevent preterm birth in twin pregnancies with regard to both maternal and neonatal outcomes. Study design: In this systematic review and meta-analysis, the PubMed, Cochrane Library, Medline, EMBASE, and Web of Science databases were searched for relevant studies and trials from their inception up to December 2020. Outcomes were expressed as risk ratios and standardized mean differences in a meta-analysis model using STATA 15.0 software. Results: The search included 944 studies, 15 of which were eligible for inclusion, representing 726 patients treated with cervical cerclage and 8578 non-cerclage treatment controls. When the cervical length was <15 mm, the risk ratio of preterm birth at <37 weeks (0.77, p = 0.01), <34 weeks (0.58, p = 0.002), and <32 weeks (0.61, p = 0.024) of gestation in the cerclage group was significantly lower than that in the non-cerclage group. Conclusion: For twin pregnancies with a cervical length <15 mm, cervical cerclage was associated with significant reduction in preterm birth.